2019
DOI: 10.1111/liv.14262
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA prevents rifampicin‐induced liver injury by regulating BSEP/NTCP expression via epigenetic activation of NRF2

Abstract: Background & AimsRifampicin (RFP)‐induced cholestatic liver injury is characterized by impaired hepatic bile acid (BA) transport. Bile salt efflux pump (BSEP) and Na+/taurocholate cotransporter (NTCP) are the major BA transporters. However, little is known about the mechanisms underlying these transporters.MethodsThe role of tanshinone IIA (TAN IIA) in preventing RFP‐induced liver injury was evaluated in vitro and in vivo, based on the regulatory mechanism of nuclear factor erythroid 2‐related factor 2 (NR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…Tan IIA administration is associated with improvement in silicamediated pulmonary inflammatory response, structural damage and fibrosis via Nrf2/ARE activation [121]. Furthermore, Tan IIA prevents liver injury via epigenetic activation of Nrf2 and reinforcing antioxidant defense system [122]. Hence, Tan IIA stimulates Nrf2 signaling as a way of recovering redox homeostasis and inhibiting pulmonary fibrosis [123].…”
Section: Natural Compounds In Ameliorating Doxorubicin-mediated Toxicitymentioning
confidence: 99%
“…Tan IIA administration is associated with improvement in silicamediated pulmonary inflammatory response, structural damage and fibrosis via Nrf2/ARE activation [121]. Furthermore, Tan IIA prevents liver injury via epigenetic activation of Nrf2 and reinforcing antioxidant defense system [122]. Hence, Tan IIA stimulates Nrf2 signaling as a way of recovering redox homeostasis and inhibiting pulmonary fibrosis [123].…”
Section: Natural Compounds In Ameliorating Doxorubicin-mediated Toxicitymentioning
confidence: 99%
“…Tanshinone IIA is a lipid-soluble natural compound isolated from the medicinal herb Salvia miltiorrhiza Burge and associated with cardiovascular and cerebrovascular protective effects. The involvement of epigenetic mechanisms in the induction of Nfe2l2 by Tanshinone IIA has been demonstrated in TPA-induced neoplastic transformation of JB6 P+ cells [ 95 ] and in in vitro and in vivo models of rifampicin-induced liver injury [ 96 ]. Hypomethylation of the N fe2l2 promoter was mechanistically linked to potent induction of Nfe2l2 mRNA and Nrf2 protein levels by Tanshinone IIA.…”
Section: Phytochemicals and The Epigenetic Regulation Of Nrf2 Signmentioning
confidence: 99%
“…Hypomethylation of the N fe2l2 promoter was mechanistically linked to potent induction of Nfe2l2 mRNA and Nrf2 protein levels by Tanshinone IIA. While one study reported decreased expression of Dnmts and Hdac1, Hdac3, and Hdac8 by Tanshinone IIA in JB6 P+ cells [ 95 ], another found no significant changes in DNMTs, but elevated expression of DNA demethylases, especially ten-eleven translocation 2 (TET2), in human hepatocyte L02 and Hepa RG cells [ 96 ]. The latter investigation showed that Tanshinone IIA could prevent rifampicin-induced liver injury by inducing the expression of bile salt efflux pump (BSEP) and Na+/taurocholate cotransporter (NTCP), which were directly regulated by NRF2 [ 96 ].…”
Section: Phytochemicals and The Epigenetic Regulation Of Nrf2 Signmentioning
confidence: 99%
“…9 Classical nuclear factor, farnesoid X receptor (FXR) and nuclear factor erythroid 2-related factor 2 (NRF2) play an important role in regulating bile acids efflux and uptake. 10,11 Our previous studies have shown that TAN IIA could induce the expression of NTCP by regulating NRF2. 11 However, the changes in NTCP functional activity after treatment of RFP or TAN IIA were not examined, and the relationship between NTCP expression and activity under this state is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Our previous studies have shown that TAN IIA could induce the expression of NTCP by regulating NRF2. 11 However, the changes in NTCP functional activity after treatment of RFP or TAN IIA were not examined, and the relationship between NTCP expression and activity under this state is still unknown.…”
Section: Introductionmentioning
confidence: 99%